A Single Nucleotide Polymorphism (rs4236480) in TRPV5 Calcium Channel Gene Is Associated with Stone Multiplicity in Calcium Nephrolithiasis Patients. (18th May 2015) - Khaleel, Anas; Wu, Mei-Shin; Wong, Henry Sung-Ching; Hsu, Yu-Wen; Chou, Yii-Her; Chen, Hsiang-Yin
Abstract : Nephrolithiasis is characterized by calcification of stones in the kidneys from an unknown cause. Animal models demonstrated the functional roles of the transient receptor potential vanilloid member 5 ( TRPV5 ) gene in calcium renal reabsorption and hypercalciuria. Therefore, TRPV5 was suggested to be involved in calcium homeostasis. However, whether genetic polymorphisms of TRPV5 are associated with kidney stone multiplicity or recurrence is unclear. In this study, 365 Taiwanese kidney-stone patients were recruited. Both biochemical data and DNA samples were collected. Genotyping was performed by a TaqMan allelic discrimination assay. We found that a TRPV5 polymorphism (rs4236480) was observed to be associated with stone multiplicity of calcium nephrolithiasis, as the risk of stone multiplicity was higher in patients with the TT+CT genotype than in patients with the CC genotype ( p = 0.0271 ) . In summary, despite the complexity of nephrolithiasis and the potential association of numerous calcium homeostatic absorption/reabsorption factors, TRPV5 plays an important role in the pathogenesis of calcium nephrolithiasis.